(untitled) (Bangladesh Journal of Zoology, 2023)
Seaweeds are one of the most potential aquaculture commodities in Bangladesh. It has a long back history of being used for its nutritional and pharmaceutical importance. This review summarizes seaweeds diversity and its culture, distribution and possible applications and uses in Bangladesh. Seaweed floras are distributed along the entire coastline, however, the higher abundance of these have found in the St. Martin Island, Cox’s Bazar, and Sundarbans mangrove forest periphery. These included around 200 species and belong to 94 genera. About 12 of these genera, including Hypnea, Gracilaria, Gelidium, Enteromorpha, Halimeda, Padina, Dictyota, Caulerpa, Hydroclathrus, Sargassum, Kappaphycus, and Porphyra have substantial commercial importance. A total of 5,000 metric tons of seaweeds are likely available along the entire coastline between October and April. However, seaweeds commodity and its aquaculture production have a great potential in the coastal region of Bangladesh. Furthermore, the sustainable development of this industry could bring numerous benefits such as rural development, employment opportunity and income generation, women empowerment, disease prevention, and proper utilization of land. Therefore, this sector needs more attention for its expansion activities include culture, usages and bioactive compound developments. Additionally, seaweeds cultivation could have numerous environmental benefits include ecosystem services, removal of hazardous nutrients and pollutants, metal toxicants uptake, in turn estuaries and seas tackle pollution in natural process. Bangladesh J. Zool. 50(3): 283-307, 2022